National survey of knowledge, attitude and practice of fibromyalgia among rheumatologists in China. (4th April 2013) - Mu, Rong; Li, Chun; Zhu, Jia‐Xin; Zhang, Xiao‐Ying; Duan, Tian‐Jiao; Feng, Min; Wang, Guo‐Chun; Zhang, Feng‐Chun; Li, Zhan‐Guo
Abstract: Aim: Fibromyalgia (FM) is a chronic disorder characterized by widespread musculoskeletal pain and fatigue. It is a less frequently diagnosed disease in China, thus Chinese rheumatologists may have lower awareness of FM compared with colleagues in Western countries. The aim of this study is to investigate the perceptions of FM in Chinese rheumatologists and analyze their therapeutic approach in clinical practice. Method: An anonymous questionnaire survey was conducted among a nationwide sample of Chinese rheumatologists at the 15th National Rheumatology Conference in 2010. The 20‐question survey included questions regarding background, work experience, perceptions of diagnosis and behaviors of treatment related to FM. Continuing medical education (CME) information was also collected in the survey. Results: Seven hundred and seven rheumatologists responded to the questionnaire, a response rate of 60%. Less than one‐fifth of the respondents were experienced in dealing with FM. Although most of the respondents regarded FM as a distinct pathological entity, nearly 30% of Chinese rheumatologists believed that FM was only a psychological disorder. The respondents recognized some of the FM‐related symptoms, but had limited knowledge on the diagnostic criteria. Eighty percent of the respondents declared they had difficulties in treating FM patients. However, nearly all (90.8%) respondents believed that the prognosis of FM patients was usually benign. Our data also showed that most Chinese rheumatologists were eager for CME on FM. Conclusion: The awareness and perception of FM are still low among Chinese rheumatologists. CME on FM is needed for improving the quality of health care in China.